Cat Scratch Disease Presenting as Fever of Unknown Origin Is a Unique Clinical Syndrome. (23rd November 2019) - Landes, Michal; Maor, Yasmin; Mercer, Diego; Habot-Wilner, Zohar; Bilavsky, Efraim; Chazan, Bibiana; Cohen, Regev; Glikman, Daniel; Strahilevitz, Jacob; Katzir, Michal; Litachevsky, Vladislav; Melamed, Rimma; et al.
Abstract: Background: Fever of unknown origin (FUO) is a rare manifestation of cat scratch disease (CSD). Data regarding CSD-associated FUO (CSD-FUO), particularly in adults, are limited. We aimed to study disease manifestations and long-term clinical outcome. Methods: A national CSD surveillance study has been conducted in Israel since 1991. Data are obtained using questionnaires, review of medical records, and telephone interviews. FUO was defined as fever of ≥14 days without an identifiable cause. CSD-FUO patients were identified in the 2004–2017 CSD national registry. Follow-up included outpatient clinic visits and telephone/e-mail surveys. Results: The study included 66 CSD-FUO patients. Median age was 35.5 years (range, 3–88). Median fever duration was 4 weeks (range, 2–9). Relapsing fever pattern was reported in 52% of patients, weight loss in 57%, and night sweats in 48%. Involvement of ≥1 organs occurred in 59% of patients; hepatosplenic space-occupying lesions (35%), abdominal/mediastinal lymphadenopathy (20%), ocular disease (18%), and multifocal osteomyelitis (6%) were the most common. Malignancy, particularly lymphoma, was the initial radiological interpretation in 21% of patients; 32% underwent invasive diagnostic procedures. Of the 59 patients available for follow-up (median duration, 31 weeks; range, 4–445), 95% had complete recovery; 3 patients remained with ocular sequelae. Conclusion: This is the first attempt to characterize CSD-FUO as a unique syndrome that may be severe and debilitating and often mimics malignancy. Relapsing fever is a common clinical phenotype. Multiorgan involvement is common. Recovery was complete in all patients except in those with ocular disease. Abstract : Cat scratch disease presenting as fever of unknown origin may be severe and debilitating and often mimics malignancy. Relapsing fever is a common clinical phenotype. Multiorgan involvement is common. Recovery is usually complete except in patients with ocular complications.